The Effect of Working Capital on the Profitability of Saudi Joint Stock - A Field Study of Companies Listed in The Saudi Stock Exchange – - Abdul Rahman, Najla Ibrahim; ALhomyani, Munirah Muhayl (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed at identifying the effect of working capital on the profitability of Saudi joint stock companies, and its application to the food production companies sector in the Kingdom of Saudi Arabia. To achieve the objectives of the study, the descriptive analytical approach was employed. A sample was chosen from the food industry sector in the Kingdom of Saudi Arabia, namely, two companies (Wafra and the Saudi Fish Company), during the period from 2015 to 2019. The study based on the financial analysis of the published financial statements of the study sample companies. In order to examine the hypotheses, and describe the relationship between the variables, and then analyze them, the statistical packages program SPSS version 22 was employed. The results of the study revealed that there is a statistically significant effect at the level of 5% between working capital and the profitability of the company, in the return on ownership rights, and there is no significant relationship A statistic at a significant level of 5% between working capital and the earnings per share index in food production companies. There is also a variance between the two companies in the effect of working capital on the return on equity. The study recommended paying attention to and monitoring the management of working capital in all its components. Conducting more studies on food production in the Kingdom of Saudi Arabia. It also recommended conducting more studies using other profitability measures.
Keywords: working capital management; Saudi industrial companies; profitability